2021
DOI: 10.1186/s12931-021-01617-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential interactions between the TBX4-FGF10 and SHH-FOXF1 signaling during human lung development revealed using ChIP-seq

Abstract: Background The epithelial-mesenchymal signaling involving SHH-FOXF1, TBX4-FGF10, and TBX2 pathways is an essential transcriptional network operating during early lung organogenesis. However, precise regulatory interactions between different genes and proteins in this pathway are incompletely understood. Methods To identify TBX2 and TBX4 genome-wide binding sites, we performed chromatin immunoprecipitation followed by next-generation sequencing (ChI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Our reporter system was designed using the standard T-BOX motif and FGF10 promoter sequences. A recent report of TBX4 chromatin immunoprecipitation in human fetal lung fibroblasts identified several other potential genome-wide target sites whose effects we have not tested ( 39 ). Therefore, a variant shown to have a modest or benign effect by our luciferase assay may still have significant damaging effects on interactions with other crucial binding sites in biologically relevant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our reporter system was designed using the standard T-BOX motif and FGF10 promoter sequences. A recent report of TBX4 chromatin immunoprecipitation in human fetal lung fibroblasts identified several other potential genome-wide target sites whose effects we have not tested ( 39 ). Therefore, a variant shown to have a modest or benign effect by our luciferase assay may still have significant damaging effects on interactions with other crucial binding sites in biologically relevant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our reporter system was designed using the standard T-BOX motif and FGF10 promoter sequences. A recent report of TBX4 chromatin immunoprecipitation in human fetal lung fibroblasts identified several other potential genome-wide target sites whose effects we have not tested (38).…”
Section: Limitationsmentioning
confidence: 87%
“…Our reporter system was designed using the standard T-BOX motif and FGF10 promoter sequences. A recent report of TBX4 chromatin immunoprecipitation in human fetal lung fibroblasts identified several other potential genome-wide target sites whose effects we have not tested (38). Therefore, a variant shown to have a modest or benign effect by our luciferase assay may still have significant damaging effects on interactions with other crucial binding sites in biologically relevant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In murine studies, Foxf1 + cells were shown to encompass a stem cell subset of collagen 1-expressing mesenchymal cells with clonogenic potential and capacity to generate lung epithelial organoids [24]. Interactions between FOXF1 and sonic hedgehog (SHH), T-box transcription factor (TBX4), TBX2 and FGF10 pathways have been described, proposing an essential transcriptional network during early lung organogenesis [25]. SCN7A encodes an atypical sodium channel.…”
Section: Discussionmentioning
confidence: 99%